Mediating Effect of Customer Satisfaction on Service Quality and Trust Relationship in Malaysian Banking Industry - Zahir Osman,; Ratna Khuzaimah Mohamad,; Liana Mohamad, (2016)
The aim of this study is to develop a mediating effect understanding of customer satisfaction on service quality and trust relationship in Malaysia commercial banking industry. The model was developed and later tested by adopting the partial Least Square (PLS) procedure on data collected from a survey that yielded 512 usable questionnaires. The findings showed that service quality boosts satisfaction in Malaysia commercial banking. It was also exposed that satisfaction partially mediates the relationship between service quality and trust. In future, more research needs to be carried out to explore the role of satisfaction in Malaysia banking industry. It is important to do the study utilizing experimental design by capturing longitudinal data in Malaysia banking industry using robust measures. The findings suggest that the relationship between satisfaction and profitability may reside in satisfaction’s influence on trust, and that satisfaction plays a crucial function within the Malaysia banking industry. This research is one of the first known attempts to use PLS to test a mediation effect. (Abstract by author)